Marriage and family in the culture of the Russian peasantry of the Western Siberia in the second half of the XIX century - Irina Sergeevna Ivanchenko (Вестник Майкопского государственного технологического университета, 2023)
The purpose of the research is to trace the evolution of family and marriage relations of the Russian peasantry of the Tobolsk province, which took place in the second half of the 19th century and was influenced by Russian reforms and modernization. The article analyzes the changes that began during this period in the institutions of family and marriage, and also considers new forms of family and marriage relations that began to appear in the peasant society. The preconditions and reasons for the weakening of the institution of the family, divorces in peasant families have been analyzed, the factors of the formation of new forms of marriage and living in fornication have been considered. The role of the state in solving family problems of the peasantry as a whole during the reform period has been investigated. As a result of the research, it has been shown that as a result of the reforms and the subsequent changes in the life of the peasant population of the Tobolsk province, the influx of migrant peasants from the European part of Russia to the region, the construction of the Trans-Siberian railway and other transformations, the form of marriage and family relations among peasants changed, new types of marriage appeared, number of divorces and unmarried women increased. The scientific novelty of the research lies in the formulation of conclusions about the crisis in the post-reform period of the patriarchal model of the multigenerational family among the Russian peasantry of the Tobolsk province (as in the rest of Russia), the spread of small family forms, the growth in the number of divorces, various models of fornication, etc.